Darbepoetin alfa for anemia with myelodysplastic syndrome. Issue 2 (April 2015) - Seastone, David J; Gerds, Aaron T
<x xml:space="preserve">Abstract</x> The myelodysplastic syndromes are characterized by refractory cytopenias that lead to symptomatic anemia, bleeding, and increased risk for infections. For almost two decades, the use of darbepoetin and other erythropoietin stimulating agents to treat symptomatic anemia in lower-risk myelodysplastic syndromes has been a standard of care. This practice is supported by numerous Phase I/II studies and one Phase III study demonstrating the benefit of using erythropoietin stimulating agents alone, or in combination with granulocyte colony stimulating factor, for treatment of symptomatic anemia with the goal of decreasing red blood cell transfusion requirements. This review summarizes the published experience regarding the use of erythropoietin stimulating agents, with a special focus on darbepoetin, in patients with myelodysplastic syndrome and symptomatic anemia.